Types of health insurance and its utilization in a primary, secondary and tertiary care setting in coastal Karnataka - Baisil, Sharon; Sathyanath, Shreyaswi; Kundapur, Rashmi (International Journal Of Community Medicine And Public Health, 2017)
Background: Health insurance as a tool to finance health care has very recently gained popularity in India. While health insurance has a long history, the upsurge in breadth of coverage can be explained by a serious effort by the Government to introduce health insurance for the poor in last four years. Objective of this study is to determine the types of health insurance prevalent in coastal Karnataka and to study its advantages in decreasing out of pocket expenditure. Methods: A cross sectional study was done among 450 patients by administering a validated questionnaire on health insurance with details, coverage amount, presence of APL or BPL card and utilization pattern with advantages to the patient from scheme. Results: Out of the 450 patients have been surveyed, 57% had availed health insurance. 35% of patients were benefited by sampoorna suraksha and 27.5% patients used KSHEMA health card. ESI and kadamba were least used. Unlimited slab was seen with aarogya bhagya and yashaswini schemes. 65% of APL category and only 35% of BPL had health insurance. 92.5% of the patients with health insurance surveyed used private hospitals for health assistance. In 25% of people, hospital visits increased due to health insurance. In 15% of patients the total expenditure on health has increased after obtaining health insurance. Conclusions: 57% of the patients had some form of health insurance. Sampoorna suraksha was the most commonly used scheme and health insurance was most commonly used for in patient care.